Abiraterone acetate for chemotherapy-naive metastatic castration-resistant prostate cancer: a single-centre prospective study of efficacy, safety, and prognostic factors - Liancheng Fan; Baijun Dong; Chenfei Chi; Yanqing Wang; Yiming Gong; Jianjun Sha; Jiahua Pan; Xun Shangguan; Yiran Huang; Lixin Zhou; Wei Xue (BMC Urology, 2018)
Abstract Background To evaluate the efficacy and safety of abiraterone acetate (AA) plus prednisone compared with prednisone alone in Asian patients with chemotherapy-naive metastatic castration-resistant prostate cancer (mCRPC), and to identify predictive factors. Methods We reviewed the medical records of 60 patients with chemotherapy-naive mCRPC at Renji Hospital who were treated with AA plus prednisone (n = 43) or prednisone alone (n = 17). All patients were assessed for prostate-specific antigen (PSA) response, PSA progression-free survival (PSA PFS), radiographic progression-free survival (rPFS), and overall survival (OS). The ability of several parameters to predict PSA PFS, rPFS, and OS was studied. Results The median follow-up time was 14.0 months (range 7.0–18.5 months), at which time 19 death events had been reported: 11 in the AA + prednisone group and 8 in the prednisone group. The AA + prednisone group had significantly longer median PSA PFS (10.3 vs 3.0 months, P < 0.001), rPFS (13.9 vs 3.9 months, P < 0.001), and OS (23.3 vs 17.5 months, P = 0.016) than the prednisone-alone group. The most frequently reported grade 3 or 4 adverse event in both the AA + prednisone and prednisone-alone groups was elevated alanine aminotransferase level in 5 of 43 patients (11.6%) and 2 of 17 patients (11.8%), respectively. No adverse events led to discontinuation of therapy. In multivariate analysis, time from androgen deprivation therapy (ADT) to castration resistance of ≤18 months was a determinant of shorter OS (P = 0.007). Conclusions These results support the favourable safety and efficacy profile of AA for the treatment of Asian patients with chemotherapy-naive mCRPC. Longer duration of ADT response was significantly associated with longer survival.